Development of ball surface acoustic wave gas chromatograph for environmental monitoring in spacecraft and its application on the ground. (1st July 2022) - Iwaya, Takamitsu; Akao, Shingo; Yamanaka, Kazushi; Okano, Tatsuhiro; Takeda, Nobuo; Tsukahara, Yusuke; Oizumi, Toru; Fukushi, Hideyuki; Sugawara, Maki; Tsuji, Toshihiro; Tanaka, Tomoki; Takeda, Akinobu; et al.
Abstract : For on-site analysis of surface materials on the Moon, planets, and small bodies and for the monitoring of air quality in crewed spacecraft, we have developed a portable gas chromatograph (GC) equipped with a ball surface acoustic wave (SAW) sensor. In this study, we fabricated a 10 cm cube GC that implements the forward flush method using two metal micro-electro-mechanical-system columns coated with different stationary phases in microchannels fabricated by wet etching and diffusion bonding of stainless-steel plates. Using this GC, we succeeded in analyzing 10 kinds of gas within 10 min. In addition, for the application of the ball SAW GC on the ground, we also developed a palm-sized GC with a single metal capillary column and used it in the analysis of the headspace gas of sake. We showed that the ratio of peak areas differed among odorants depending on the brand and brewing process of sake.